P118 Procalcitonin can reduce antibiotic usage in patients with suspected respiratory infections in an acute respiratory service. (15th November 2017) - Elfaki, H; Parsons, H; Cawthron, K; Holborn, A; Pirzada, O
Abstract : Introduction: Procalcitonin (PCT) guidance can help safely decrease antibiotic exposure in patients with suspected or confirmed respiratory infections. 1 Its use however across UK hospitals remains limited. We set out to see if utilising it in an acute respiratory service will aid consultant decision making and reduce unnecessary antibiotic usage. Methods: A case series of 222 patients with suspected respiratory infections were consecutively included over 3 months. Their records where examined retrospectively. A PCT result of <0.25 µg/L would have suggested no potential need for antibiotics. Results: 75 patients (34%) with a COPD exacerbation; 45 (20%) a lower respiratory tract infection; 34 (15%) community acquired pneumonia; 17 (8%) asthma exacerbation; 13 (6%) Hospital acquired pneumonia; 11 (5%) Exacerbation of bronchiectasis; 10 (4%) aspiration pneumonia; 17 (8%) with other conditions, not a primary respiratory infection. 172 patients (77%) had a PCT of<0.25 µg/L and 50 (23%)≥0.25 µg/L. In 96 patients (56%) with a low PCT, consultants decided not to prescribe antibiotics: stopped in 56 (33%) and not started in 40 (23%). In 76 patients (44%) the consultant prescribed antibiotics: continued in 32 (19%); started in 28 (16%) and in 16 (9%) switched to another antibiotic. Bronchiectasis and Aspiration pneumonia patients were more likely to get Antibiotics despite low PCT, 6 patients in both groups (54%) and (60%) respectively. Lower respiratory tract infections and Hospital acquired pneumonia patients were less likely to be given antibiotics if the PCT was low, 9 patients (20%) in the first group and 3 (23%) in the second. In Patients with a PCT level≥0.25 µg/L 45 (90%) received antibiotics. Conclusion: Low levels of Procalcitonin can reduce antibiotic usage in patients admitted with respiratory infections. This could have an effect on reducing the risk of antimicrobial resistance and costs associated with antibiotic prescriptions. Apprehension remains among respiratory physicians in utilising it as expressed in the number of patients who had antibiotics despite low PCT levels. The validation of the test in conditions like Bronchiectasis and aspiration pneumonia requires further evidence. Reference: Christ-Crain M, et al. Lancet2004;363:600–7.